Hydrologically contrasting environments induce genetic but not phenotypic differentiation in Solanum dulcamara. (12th September 2016) - Zhang, Qian; Peters, Janny L.; Visser, Eric J. W.; de Kroon, Hans; Huber, Heidrun
Summary: In contrasting habitats, locally adapted populations are expected to evolve through directional selection. Hydrological gradients provide a scenario where strong selection forces have led to species segregation in communities along the hydrological niche axes due to specific adaptations to their ambient environment. However, much less is known about the processes enabling species with wide ecological amplitudes, such as Solanum dulcamara L., to occupy the contrasting niches at the far ends of the gradient. Here, we investigate the question whether local adaptation is indeed the driving mechanism enabling this species to inhabit contrasting wet and dry habitats. Using molecular analyses and performing a common garden experiment, we examined whether genetic and phenotypic differentiation had occurred between populations originating from flooding‐ and drought‐prone habitat pairs from nine different locations. We also tested whether plants were better adapted to their home site stress. We found a significant genetic variation but hardly any phenotypic differentiation between populations from contrasting habitats for plants grown under optimal conditions. Surprisingly, comparison of the genetic differentiation in neutral markers with that in phenotypic traits using the Q ST ‐ F ST (estimated by ФPT ) approach revealed that the Q ST values were consistently and significantly smaller than the ФPT values. This is in contrast to the hypothesis that directional selection is an important component enabling S. dulcamara to survive under contrasting habitat conditions. In addition, no home site effects were detected for responses to flooding and drought treatments. All plants were characterized by high levels of plasticity for traits associated with flooding and drought tolerance, such as rapid adventitious root formation upon flooding and increased root to shoot ratio in response to drought, irrespective of habitat of origin. Moreover, no trade‐offs in such flooding and drought responses were found. Synthesis . Our results show that S. dulcamara has not evolved locally adapted populations in response to flooding and drought stress, despite genetic differentiation and despite the presumably strong selection gradient. The generally high levels of adaptive plasticity in traits increasing flooding and drought tolerance may be the main mechanism allowing S. dulcamara to occupy hydrologically contrasting habitats. Abstract : By comparing plants from contrasting habitats, this paper shows that S. dulcamara has not evolved locally adapted populations in response to flooding and drought stress, despite genetic differentiation and despite the presumably strong selection gradient. The generally high levels of adaptive plasticity in traits increasing flooding and drought tolerance may be the main mechanism allowing S. dulcamara to occupy hydrologically contrasting habitats.